From incarnation to re-incarnation - Ingalese, Richard (The Occult book concern, 1904)
The relation of sex.--Marriage.--Parenthood.--Physical and psychic development.--Mental and spiritual development.--Focusing forces.--Mental repulsion.--Mental attraction.--Death.--After death.